Sexually transmitted shigellosis - Pirš, Mateja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2024)
Shigellae can be transmitted through sexual contact, especially among gay, bisexual, and other men who have sex with men (gbMSM). The dynamics and factors contributing to sexual transmission of shigellosis are not yet fully understood. Shigella spp. are intestinal pathogens with a low infectious dose, making them more likely to spread through sexual contact. Asymptomatic carriage may also contribute to its transmission through sexual activity. Recommendations for prevention of sexual transmission of shigellosis include less risky sexual behavior, the use of protective measures, thorough cleaning of sex toys, and good personal hygiene. If a partner has diarrhea, it is recommended to avoid sexual contact during and for at least 1 to 2 weeks after the symptoms have resolved, and to refrain from oral-anal contact for 4 to 6 weeks. Globally, the burden of shigellosis is highest in low- and middle-income countries, particularly among young children. In high-income countries, international travelers and gbMSM are considered the main risk groups for shigellosis. Raising awareness about the possible sexual transmission of shigellosis among at-risk groups is necessary. Increasing awareness among clinicians about the potential for sexual transmission of shigellosis is vital to ensure appropriate counseling and patient management.
Keywords: genotipizacija; odpornost na antibiotike; preventiva; spolno prenosljiva šigeloza; strategija nadzora javnega zdravja; šigeloza